Molecular Characterization of Methicillin-Resistant Staphylococcus aureus Isolates, Isolated from a Burn Hospital in Southwest Iran in 2006 and 2014 - Ehsanollah Ghaznavi-Rad; Alireza Ekrami (International Journal of Microbiology)
Objectives. Incidence of methicillin-resistant Staphylococcus aureus (MRSA) is increasing every year, especially in burn patients with a high rate of morbidity and mortality. Molecular and epidemiologic studies are useful practices for understanding the relatedness of isolates in a single patient or a hospital. This study aimed at determining molecular characterizations of isolates collected in 2006 and 2014 using S. aureus-specific staphylococcal protein A (Spa) typing and Multilocus Sequence Typing (MLST) methods. Materials and Methods. Totally, 71 MRSA isolates were collected during the last two studies (2006 and 2014) from burn patients at Taleghani Burn Centre. After confirmation, all isolates were analysed using MLST and Spa typing methods. Results. We reported the emergence of Spa type t021, ST-30-IV MRSA isolates, which were PVL-positive in 14.6% of the cases and t12366, ST-8-IV isolates, which were PVL-negative in 9.8% of the cases. In 2014 study, Spa typing of MRSA isolates revealed five different spa types. Overall, in two studies, t037, ST-239, SCCmec III, and CC8 were predominant clones and they were reported in 63% of the cases. Conclusion. The predominance of ST-239 in this region during the last eight years is a major concern. It also has a disturbing impact on the management of staphylococcal infections. Moreover, the SCCmec type IV strain is able to disseminate rapidly in hospital environments, demanding an improvement in infection-control policy.